Clinical pharmacology - Bennett, Peter N. (Churchill Livingstone/Elsevier, 2012)
A thorough knowledge of pharmacological and therapeutic principles is vital if drugs are to be used safely and effectively for increasingly informed patients. Those who clearly understand how drugs get into the body, how they produce their effects, what happens to them in the body, and how evidence of their therapeutic effect is assessed, will choose drugs more skilfully, and use them more safely and successfully than those who do not. Now in a fully revised 11th edition, Clinical Pharmacology is essential reading for undergraduate medical students, junior doctors and anyone concerned with evidence-based drug therapy.